2020
DOI: 10.3390/catal10101126
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Anatase–Rutile Diphase N-doped TiO2 Nanoparticles with Excellent Visible Light Photocatalytic Activity

Abstract: To further boost the charge separation and photocatalytic activity of TiO2 under visible light, the anatase–rutile mixed-phase nitrogen-doped (N-doped) TiO2 nanoparticles were successfully synthesized through a facile one-step calcining procedure using TiN as raw materials. The crystal phases, morphologies, chemical compositions, textural structures, and optical properties of as-obtained N-doped TiO2 were characterized by the corresponding analytical techniques. The photocatalytic activities of as-fabricated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…In addition, the binding energy of N 1s photoelectron highly depends on the method employed to synthesize the Ndoped TiO 2 nanoparticles [35]. In the present study, N 1 s peak observed at 400.7 eV could be attributed to the interstitial N of the N-doped TiO 2 with an O−Ti−N linkage [36] which is also in consistent with the XPS results of N-doped TiO 2 reported by Liu et al [37]. Moreover, the presence of this nitrogen in the N-doped TiO 2 has led to reduction of TiO 2 bandgap as well.…”
Section: Characterization and Performancesupporting
confidence: 92%
“…In addition, the binding energy of N 1s photoelectron highly depends on the method employed to synthesize the Ndoped TiO 2 nanoparticles [35]. In the present study, N 1 s peak observed at 400.7 eV could be attributed to the interstitial N of the N-doped TiO 2 with an O−Ti−N linkage [36] which is also in consistent with the XPS results of N-doped TiO 2 reported by Liu et al [37]. Moreover, the presence of this nitrogen in the N-doped TiO 2 has led to reduction of TiO 2 bandgap as well.…”
Section: Characterization and Performancesupporting
confidence: 92%
“…Subsequently, the current approaches a constant value, which describes the permanent flow of charges. The fact that the initial current peak is higher in doped samples is due to the initial excitation of more charge carriers and a better charge separation in samples with higher crystallinity . The higher photocurrent at lower wavelengths is due to the excitation of more charge carriers at higher incident photon energies allowing the direct excitation of electrons from the valence into the conduction band .…”
Section: Resultsmentioning
confidence: 99%
“…The fact that the initial current peak is higher in doped samples is due to the initial excitation of more charge carriers 40 and a better charge separation in samples with higher crystallinity. 41 The higher photocurrent at lower wavelengths is due to the excitation of more charge carriers at higher incident photon energies allowing the direct excitation of electrons from the valence into the conduction band. 42 TDRS measurements revealed that the population of surface-trapped electrons decreased more strongly in N-doped titania than in pure TiO 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The obtained BET curves showed typical type IV with type H 3 hysteresis loops according to the International Union of Pure and Applied Chemistry (IUPAC) classification for both TiO 2 and TiON samples. This observed characteristic of the samples can be attributed to the presence of interparticle porous structures formed in both bare TiO 2 and TiON. , The obtained pore size distribution curves (BJH) indicated the existence of a narrow distribution of pores in the TiON system, with a mean pore size of ∼9.7 nm (inset of Figure b), while the distribution is relatively broader for bare TiO 2 , with a mean decreased pore size of ∼7.2 nm (inset of Figure a). This represents that TiON can possibly have a stable, homogeneous, and reactive surface, which is much more compatible for the sensitizer deposition interaction.…”
Section: Resultsmentioning
confidence: 99%